2005
DOI: 10.1007/s10344-005-0085-0
|View full text |Cite
|
Sign up to set email alerts
|

Feral donkey Equus asinus populations on the Karpaz peninsula, Cyprus

Abstract: Numerous researchers have documented the adverse effects of feral donkeys Equus asinus introduced to semi-arid ecosystems. With the release of feral donkeys and potential increasing populations in natural habitats in northern Cyprus, there is concern for negative impacts on vegetation and native species. In the north of the island, there has been only one published study of feral donkey populations, and population estimators were relatively subjective. We estimated feral donkey populations on the Karpaz Penins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 8 publications
(11 reference statements)
1
8
0
1
Order By: Relevance
“…However the number of the Cypriot donkeys is drastically reducing as well as the Anatolian donkeys (11). Hamrick et al (7) reported that 800 donkeys were in Karpaz peninsula in 2003.…”
Section: Discussionmentioning
confidence: 99%
“…However the number of the Cypriot donkeys is drastically reducing as well as the Anatolian donkeys (11). Hamrick et al (7) reported that 800 donkeys were in Karpaz peninsula in 2003.…”
Section: Discussionmentioning
confidence: 99%
“…In some areas, feral and free-roaming donkeys are able to live natural lives; they live in self-defined groups, are able to freely express their natural behaviour and adapt to local ecological conditions [58,59]. However, in other areas, they may be seen as 'pests', 'invasive species' or 'vermin' and are subject to aggressive measures for population control or eradication [53,[60][61][62]. In both contexts, feral donkeys can suffer from significant welfare problems [59] but the assessment of welfare in these contexts is lacking.…”
Section: (D) Feral Equidsmentioning
confidence: 99%
“…En la actualidad se encuentra distribuida en todo el continente. A nivel mundial, muchos estudios demuestran los efectos adversos que las poblaciones de esta especie han generado en aquellas áreas donde han sido introducidos (Gordon and Illius 1989;Mishra et al 2004;Hamrick et al 2005;Australian Government 2011). En un ambiente natural, el mayor problema que generan es el ocasionado por competencia por alimento y agua con la fauna nativa, además de impactar fuertemente sobre las comunidades vegetales y la estructura del suelo (Álvarez Romero and Medelllín 2005;Beever and Aldridge 2011).…”
Section: Introductionunclassified